(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
This article shows the design, production, analysis, control, and experimental activities in which is considered to be a suitable engineering education. The design for a motor powered weeder is performed for home gardening labour has been detailed. In India over the last 20 years, labour saving and efficiency have been required since the involvement in agricultural industry was reduced to 50 percent. An electric powered weeder design is developed because this is concerned with environment, agriculture, and engineering. Design and manufacturing is the core to engineering, education for mechanical engineering requires the concept of practical design and manufacturing. The initial aim is the development and manufacturing of a weeder via a rotating body and the mechanical component that nails up and down. The second is stress analysis and control experimental validation of the weeder.